2021
DOI: 10.1039/d0cc07371g
|View full text |Cite
|
Sign up to set email alerts
|

Highly crystalline Na0.5Bi0.5TiO3 of a photocatalyst valence-band-controlled with Bi(iii) for solar water splitting

Abstract: Highly crystalline Na0.5Bi0.5TiO3 as a photocatalyst valence-band-controlled with Bi(iii) split water under simulated sunlight irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Because of having exceptional piezoelectricity and pyroelectricity, relaxor FE Na 0.5 Bi 0.5 TiO 3 (NBT, E g = 3.1 eV) [ 130 ] serves as an important lead‐free system, which also exhibits decent photovoltaic effect and photocatalytic activity in water splitting. [ 131,132 ] As for its ground‐state structure, the decades‐long issue [ 133 ] reaches a general consensus until affirmation of a monoclinic (Cc) phase, [ 134,135 ] which arises from Na/Bi positional disorder. By suppressing this disorder via poling, the average Cc phase irreversibly transforms into the R3c phase.…”
Section: Electrostatic Energy Storage Systemsmentioning
confidence: 99%
“…Because of having exceptional piezoelectricity and pyroelectricity, relaxor FE Na 0.5 Bi 0.5 TiO 3 (NBT, E g = 3.1 eV) [ 130 ] serves as an important lead‐free system, which also exhibits decent photovoltaic effect and photocatalytic activity in water splitting. [ 131,132 ] As for its ground‐state structure, the decades‐long issue [ 133 ] reaches a general consensus until affirmation of a monoclinic (Cc) phase, [ 134,135 ] which arises from Na/Bi positional disorder. By suppressing this disorder via poling, the average Cc phase irreversibly transforms into the R3c phase.…”
Section: Electrostatic Energy Storage Systemsmentioning
confidence: 99%
“…The band gap of Bi-TLO (3.30 eV) was smaller than that of CsTLO (3.60 eV), indicating the band gap narrowing effect when Bi 3+ was incorporated. Substitution of La 3+ in Na 0.5 La 0.5 TiO 3 by Bi 3+ resulted in the band gap narrowing of 0.3 eV due to the hybridized orbitals between O 2p and Bi 6s at the valence band . The energy band diagram of Bi-TLO is drawn in Figure S2 (the detailed calculation is shown in the Supporting Information), where the VB shifted upward with respect to that of CsTLO.…”
Section: Resultsmentioning
confidence: 99%
“…However, pure NBT exhibits a wide band gap of (∼3.10 eV) which hinders visible-light-driven photocatalysis. To overcome this issue, recently, NBT-based ternary composite RhCr 2 O x /Na 0.5 Bi 0.5 TiO 3 /CoOOH has been reported by Watanabe et al which showed overall photocatalytic water splitting with significant high rates of H 2 (102 μmol h –1 ) and O 2 generation (50 μmol h –1 ) due to the suitable alignment of conduction band (CB) and valence band (VB) edge. In another example, Chauhan et al reported a 20 times greater rate of Rhodamine B dye degradation with Na 0.5 Bi 0.5 TiO 3 –BiOCl composites as compared to bare NBT due to the formation of a type-II heterojunction at the interface which promotes facile charge transfer.…”
Section: Introductionmentioning
confidence: 99%